Pengaruh Media Pembelajaran Digital dan Self-Regulated Learning Terhadap Hasil Belajar - Naisa Alifah, Rafha; Marsofiyati, Marsofiyati (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study aims to analyze the influence of Digital-Based Learning and Self-Regulated Learning on Learning Outcomes. The research method used is a survey, with a sample of 30 respondents who are students of the Economics and Administration Study Program at the State University of Jakarta. Data were collected through a Likert scale-based questionnaire and analyzed using descriptive and inferential statistics with SPSS. This study shows that the relationship between Digital-Based Learning and Self-Regulated Learning on Learning Outcomes is not significant. Although theories such as Bandura (1997) and Pintrich & Zusho (2007) emphasize the importance of self-regulation in learning, the results indicate that other factors may play a larger role in determining learning outcomes. The low R² test (9.2%) and the insignificant F test (p > 0.05) indicate that there are many external factors, such as intrinsic motivation or social support, that potentially have a greater impact on learning outcomes. This research underscores the need for a comprehensive learning approach that integrates technology, interpersonal support, and the development of metacognitive skills to effectively improve students' academic outcomes.